Organizing the colonial outpost American re-establishment of Manila's architecture from 1900-1906 - Ebro, Joselito Jr. M. (Espasyo : Journal of Philippine Architecture and Allied Arts, 2014)
To establish their control and achieve the manifest destiny of benevolently assimilating their newly acquired territory in the East, the United States established policies on re-organizing the socio-political structure of the Philippine islands. Part of this endeavor was in the field of architecture. Their vision of a colonial city was actualized through the developments set in their colonial outpost, the city of Manila. In this process, the early years of American efforts in reorganizing the colonial architecture of Manila proved to be influential in shaping the policies and improvements set by the American in the following years. From 1900 to 1906, the city of Manila underwent a series of improvements as seen through the introduction of modern architectural styles, the use of suitable materials and the application of more advanced methods of construction. The creation of agencies and the appointment of competent urban planners also contributed to the inauguration of the promising future of the city's landscape.